The Hidayatullah Organization in Community Development in Remote Villages Across Indonesia - Muna Zakiyyah; Taufik Fuzan Ginanjar (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study examines the role of the Hidayatullah Organization in fostering community cadres in remote rural areas of Indonesia, particularly in regions with limited access to formal education. The organization implements a comprehensive development model through various non-formal educational activities, such as regular religious study sessions, leadership training, and character-building programs, which are designed to cultivate potential leaders from grassroots communities, including farmers and individuals from modest economic backgrounds. The approach not only emphasizes strengthening religious understanding but also integrates economic empowerment initiatives, such as small-scale business training based on mutual cooperation, as a response to structural poverty in remote areas. Based on case studies conducted in several villages, the program has been shown to enhance community participation in village development, strengthen social cohesion, and produce local figures who actively contribute to driving positive change. Overall, the findings indicate that this development model plays a significant role in reducing development disparities and holds strong potential for replication in other regions with similar characteristics.